Contending issues of the moment : essays in public policy analysis - Yahaya, A. D. (Topo, Badagry, Lagos : Administrative Staff College of Nigeria (ASCON), 1992)
The book contains three lectures with their various tittles. It is meant to address contemporary issues of profound significance in the present debate on "The Changing Role of the State". It does not cover the whole field of public administration. Rather, they are thought on only three of the topical issues of the moment in the domain of public policy analysis.
Includes bibliographical references.
hza 16/07/2018
Loans
Keywords: Public administration; Nigeria